Trois nouveaux noms nord-africains transcrits en latin : Iarvacchius, Lemlamitanus et Amizauan, d’après des sources épigraphiques récemment découvertes en Algérie - Zouhir Bakhouche (Multilinguales)
Three recently discovered Latin inscriptions have just enriched the epigraphic and onomastic folder of two ancient sites in Algeria. Two of these three documents (comprising votive texts) were unearthed during a clandestine excavation at the site of “Henchir El-Qsiba” (the ancient Civitas Popthensis), located 64 km northeast of Souk Ahras. In addition, a third funerary stele has been found in a location known as "El-Zaouia" in "Djebel Chechar" (south of Khenchela) after June 2018’s heavy rains. First, a succinct overview of the two sites will be included in this paper. After that, we shall handle the information pertaining to every one of the unpublished steles using an archaeo-descriptive approach, to which we have added the lecture of three (03) inscriptions, according to a methodology proper for the epigraphist. Furthermore, a number of previously unknown names to the onomastic lists of African names recorded in Latin during the Roman period were the subject of a specific investigation, they are in fact : two anthroponyms : IARVACCHIUS (Gentilicium), AMIZAUAN (unique name) and one ethnonym (unicum) : LEMLAMITANI.